L’influence du cadre juridique sur la distribution des produits d’assurance en France - Venard, Bertrand (Assurances)

(untitled) (HEC Montréal, 1995)
Each economic sector is influenced by some environmental components, such as consumer demand, competition, technology, the legal framework,... Thus, insurance is characterized by a compulsory contractual relation between the parties and one can then think first of all that the legal framework is very powerful in explaining the structures for this sector. One specific point is the organization of insurance product distribution. Our purpose is to briefly present the French legal framework in respect to non-life insurance and to highlight a few particular points explaining non-life insurance distribution, especially through exclusive agents.